2014
DOI: 10.1172/jci69073
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial HIF-2 mediates protection and recovery from ischemic kidney injury

Abstract: The hypoxia-inducible transcription factors HIF-1 and HIF-2 mediate key cellular adaptions to hypoxia and contribute to renal homeostasis and pathophysiology; however, little is known about the cell type-specific functions of HIF-1 and HIF-2 in response to ischemic kidney injury. Here, we used a genetic approach to specifically dissect the roles of endothelial HIF-1 and HIF-2 in murine models of hypoxic kidney injury induced by ischemia reperfusion or ureteral obstruction. In both models, inactivation of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
143
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 65 publications
(82 reference statements)
10
143
0
2
Order By: Relevance
“…17 Studies from our group 18,19 and others 20 have demonstrated that HIF-2a plays a key protective role in renal IRI, by preserving endothelial integrity and functions. However, whether HIF-2a in T/NKT cells plays a role in renal IRI still remains to be elucidated.…”
mentioning
confidence: 97%
“…17 Studies from our group 18,19 and others 20 have demonstrated that HIF-2a plays a key protective role in renal IRI, by preserving endothelial integrity and functions. However, whether HIF-2a in T/NKT cells plays a role in renal IRI still remains to be elucidated.…”
mentioning
confidence: 97%
“…In response to I/R, ECs increase the expression of cell adhesion molecules, such as vascular cell adhesion molecule 1 (Vcam1) and Icam1, which recruit and activate circulating inflammatory cells in the kidneys. [3][4][5][6][7] The results of previous studies have demonstrated that administration of blocking antibodies against Vcam1 or Icam1 ameliorated renal I/R injury in rodents. [3][4][5] Likewise, antisense oligonucleotides for Icam1 attenuated ischemic AKI in rats.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] The results of previous studies have demonstrated that administration of blocking antibodies against Vcam1 or Icam1 ameliorated renal I/R injury in rodents. [3][4][5] Likewise, antisense oligonucleotides for Icam1 attenuated ischemic AKI in rats. 6 Moreover, Kelly et al 7 showed that Icam1-deficient mice were protected from I/R injury to the kidneys.…”
mentioning
confidence: 99%
“…HIF-1a and HIF-2a are induced by hypoxia, which can drive VEGF expression, resulting in angiogenesis (Skuli et al, 2012;Kapitsinou et al, 2014;Oh et al, 2015). Contrary to iNOS, eNOS plays constitutive roles in physiological vasodilatation and ECE-1 is also an important regulator of vascular tone Robinson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian HIFs function as heterodimers composed of either HIF-1a or HIF-2a bound to HIF-1b. HIF-1a appears to be ubiquitously expressed, whereas HIF-2a is more restricted to vascular endothelial cells (Skuli et al, 2012;Kapitsinou et al, 2014). HIFs control a series of genes that help in adaptation to hypoxia.…”
Section: Introductionmentioning
confidence: 99%